Comparison of the effectiveness of cognitive-behavioral therapy and schema therapy on sexual dysfunction in infertile women - Abbaszadeh, Azam; Khajevand Khoshli, Afsaneh; Asadi, Javanshir (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The aim of this study was to compare the effectiveness of cognitive-behavioral therapy and schema therapy on sexual dysfunction in infertile women. Method: The research method was quasi-experimental with pre-test, post-test design and follow-up with experimental and control groups. The study population was all infertile women referred to infertility centers in Sari in the first 6 months of 2019. The sample consisted of 60 people who were selected by purposive sampling method and randomly assigned to three groups of cognitive-behavioral therapy (20 people), schema therapy (20 people) and control (20 people). The first experimental group received cognitive-behavioral therapy (Becky, Owen and Wright, 2019) and the second experimental group received Young Schematic Therapy (2006) in 8 sessions of 90 minutes. The research instruments were Rosen et al.'s (2000) Sexual Performance Index Questionnaire. Data were analyzed by repeated measures analysis of variance using SPSS-22 software. Results: The results showed that cognitive-behavioral therapy and schema therapy improved sexual dysfunction and subscales of sexual desire (F=12.86, P